A collagen telopeptide binding peptide shows potential in aiding collagen bundle formation and fibril orientation. (26th June 2017) - Yang, Wenyu; Li, Lin; Su, Guanghao; Zhang, Zhe; Cao, Yiting; Li, Xuemin; Shi, Yanping; Zhang, Qiqing
Abstract : A double-armed CTBP-PEG-CTBP derivative of a collagen telopeptide binding peptide (CTBP), shows potential in aiding collagen bundle formation and fibril orientation by interacting with fibrils. Abstract : Type I collagen, the main component of the extracellular matrix (ECM), assembles into bundles, which are then arranged in an orderly manner in many tissues. Various in vitro methods have been developed to mimic this native characteristic to create aligned, collagen-based materials for constructing tissue-engineered organs. In this study, we examined a new strategy to enhance collagen bundle formation and fibril orientation through administration of a collagen telopeptide binding peptide (CTBP). We found that CTBP, or a double-armed CTBP-PEG-CTBP derivative, could interact with both individual collagen molecules and fibrils. The CTBP interaction with collagen molecules inhibited fibril formation, whereas with reconstituted collagen fibrils, CTBP-PEG-CTBP promoted collagen bundle formation and fibril orientation. Finally, the addition of the CTBP derivative to the collagen matrix showed good cellular compatibility during in vitro cell culture. Taken together, our findings suggest that CTBP may have the potential for creating orderly, aligned, collagen-based matrices for tissue engineering.